Iatrogenic Botulism After Cosmetic Use of Botulinum Toxin‐A: A Case Series - Mohammad Asadi; Shahin Shadnia; Babak Mostafazadeh; Peyman Erfan Talab Evini; Faraz Zandieh; Mitra Rahimi (Clinical Case Reports)
ABSTRACT Botulism symptoms after cosmetic botulinum toxin‐A (BTX‐A) injections happen very rarely, and it needs careful attention since it can be life‐threatening. Hence, it is advised to meticulously check the technique, dose, and authenticity of the BTX‐A before injections to reduce the adverse effects.